2002
DOI: 10.1039/b108584k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a triamidoamine complex of trivalent uranium

Abstract: Reduction of [U(NN'(3))I] [NN'(3) = N(CH2CH2NSiMe2But)(3)] with potassium in pentane gives the purple trivalent monomer [U(NN'(3))] in good yield, this compound having previously been synthesised via fractional vacuum sublimation of mixed-valent [{U(NN'(3))}(2)(mu-Cl)]. The magnetic susceptibility of this compound is consistent with the presence of U(III) centres, and this is confirmed by a characteristic near IR spectrum. Its reactions with Lewis bases to give e.g. [U(NN'(3))(Py)] and [U(NN'(3))(HMPA)] are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 31 publications
9
97
0
Order By: Relevance
“…17 Very early on the potential novelty of Tren-uranium complexes was highlighted by the observation that freeze-thaw degassed solutions of 11 placed under an atmosphere of dinitrogen change colour from purple to red. 17 The HMPA molecule in 14 coordinates through the oxygen atom; the NMR and absorption spectra for 13 and 14 are typical of uranium(III) species. 18 Inspection of the characterisation data for 12 initially suggested a U III -N 2 -U III bonding picture with no increase in valency for the uranium centres and a neutral N 2 ligand; however, with advances in computational and spectroscopic techniques it was later suggested that in fact the solid state data for 12 were somewhat misleading and a more likely bonding situation is that of a reduced N 2 unit coordinated to uranium(IV) centres consistent with U -N 2 backbonding.…”
Section: Uranium(iii) Derivativesmentioning
confidence: 99%
“…17 Very early on the potential novelty of Tren-uranium complexes was highlighted by the observation that freeze-thaw degassed solutions of 11 placed under an atmosphere of dinitrogen change colour from purple to red. 17 The HMPA molecule in 14 coordinates through the oxygen atom; the NMR and absorption spectra for 13 and 14 are typical of uranium(III) species. 18 Inspection of the characterisation data for 12 initially suggested a U III -N 2 -U III bonding picture with no increase in valency for the uranium centres and a neutral N 2 ligand; however, with advances in computational and spectroscopic techniques it was later suggested that in fact the solid state data for 12 were somewhat misleading and a more likely bonding situation is that of a reduced N 2 unit coordinated to uranium(IV) centres consistent with U -N 2 backbonding.…”
Section: Uranium(iii) Derivativesmentioning
confidence: 99%
“…In 2002, Scott and co-workers reported reactions between two equivalents of the U(III) complex [U(NN′ 3 15 The reactions are formally type (b) oxidative additions, whilst the NN′ 3 triamidoamine ligand acts as an inert supporting ligand. In 2009, Boncella and co-workers reported reactions between a U(V) bridging imido dimer (7) and Ph-E-E-Ph (E = S, Se, Te), which produced a series of U(VI) trans-bis-imide products (Scheme 5).…”
Section: Oxidative Addition With Uranium As the Only Electron Donormentioning
confidence: 99%
“…A few actinide metallocene hydroxides have been reported [1,2] and there are a few lanthanide analogues [3][4][5][6][7][8][9][10][11]. For the actinindes several closely related, but not formally organometallic, molecular complexes have been structurally characterized [12,13]. The preparation of f-element hydroxides generally involves controlled hydrolysis of a suitable metal precursor.…”
Section: Introductionmentioning
confidence: 98%